2018
DOI: 10.3389/fimmu.2018.02242
|View full text |Cite
|
Sign up to set email alerts
|

Marginal-Zone B-Cells Are Main Producers of IgM in Humans, and Are Reduced in Patients With Autoimmune Vasculitis

Abstract: In mice, B1 and marginal zone (MZ) B-cells play an important role in prevention of autoimmunity through production of regulatory cytokines and natural antibodies. There is limited knowledge about the human counterparts of these cells. We therefore investigated functions of MZ-like B-cells and the frequency of circulating MZ-like and B1-like B-cells in healthy controls (HC), as well as in patients with autoimmune vasculitis to learn more about the role of these cells in autoimmune disease. After stimulation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 45 publications
5
33
0
1
Order By: Relevance
“…Moreover the correlation of unswitched memory B-cells and serum IgM levels were consistent with a previous study (41). In this study marginal zone (MZ)-like B-cells (CD19 + CD27 + IgD + IgM high , comparable with unswitched memory B-cells in our study), negatively correlated with MPO-and PR3-ANCA levels, whereas we found a positive significant correlation of the changes in MPO-and PR3-ANCA levels with the changes in unswitched memory B-cells.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover the correlation of unswitched memory B-cells and serum IgM levels were consistent with a previous study (41). In this study marginal zone (MZ)-like B-cells (CD19 + CD27 + IgD + IgM high , comparable with unswitched memory B-cells in our study), negatively correlated with MPO-and PR3-ANCA levels, whereas we found a positive significant correlation of the changes in MPO-and PR3-ANCA levels with the changes in unswitched memory B-cells.…”
Section: Discussionsupporting
confidence: 92%
“…53,54 Others reported that marginal zone (MZ) B cells also contribute to natural antibody production in both humans and mice. 55,56 Serum concentrations of natural IgM are similar between mice held under standard housing conditions and those kept free of microbiota or even solid food antigens. 57 The CD5+ B-1 cells in spleen and body cavities of germfree, as well as SPF-housed, mice also showed very similar Ig-VH gene repertoires, supporting the long-held concept of "natural" IgM production, that is, production of IgM that is independent of foreign antigen.…”
Section: Natural Igm Production: Two Sides To a Coinmentioning
confidence: 97%
“…Early adoptive transfer studies showed that much of the circulating IgM was produced by these cells and subsequent studies using transfer of B‐1 cells into neonatal B cell‐depleted mice showed that amount to be more than 90% . Others reported that marginal zone (MZ) B cells also contribute to natural antibody production in both humans and mice …”
Section: Natural Igm Production: Two Sides To a Coinmentioning
confidence: 99%
“…Variables investigated included serum levels of BAFF, which are increased in people with MS ( 42 ), and anti-EBV antibodies, since EBV has been implicated in the pathogenesis of MS ( 14 ). In addition, total non-specific IgM levels were compared with CD32b expression levels on cells, since MZ-like B cells are the main producers of serum IgM ( 43 ). Serum levels of other Ig, including IgA, total IgG and IgG subclasses were also included for comparison.…”
Section: Resultsmentioning
confidence: 99%